A modelagem como proposta para a introdução à probabilidade por meio dos passeios aleatórios da Mônica - Santos, Paulo Avelino dos (2010)
In this work analyzes we consider it of the contributions that a sequência of education applied in the classroom in the inverse direction of the usual praxeologia brings for the introductory appropriation of the probability concept, that is, as the education sequence that approaches the introduction to the probability, by means of a proposal of simulation and modeling involving the random strolls of the Mônica - activity to teach basic concepts of Probabilities can favor the learning. The accomplishment of this study had as research citizens, 70 students of 8º year of Basic Ensino of the private net of education, in the city of São Paulo. We carry through our research considering the studies of Cazorla and Santana (2006), in set with the research carried through for Cazorla and Gusmão (2009) and the Group of Research AVALE , that it uses the modeling as didactic resource. To analyze the accomplishments of the students, we consider mentioned questionings e previously, mainly the question: Which the contributions that a sequência of education, applied in classroom in the inverse direction of the usual praxeologia bring for the introductory appropriation of the probability concept? , it is tied with our theoretical referencial, the Antropológica Theory of Didactic (TAD) and the studies of Nagamine, Henriques and Utsumi (2009), therefore these understand that the type of task (t), technique (), technology (θ) and theory () describe a complete praxeológica organization [t //], and still, for the suggestion of the inversion of the usual praxeologia when carrying through the study of introduction to the Probability. We idealize our work focus on teaching experiment, based in a research-action, given to the interaction between the researcher and the students, and considering that our intention was to verify if the process of simulation and modeling it can, or not, to favor the education of probability in Basic Educacion of experimental form